Organophosphate esters in dust samples collected from Danish homes and daycare centers. (July 2016) - Langer, Sarka; Fredricsson, Malin; Weschler, Charles J.; Bekö, Gabriel; Strandberg, Bo; Remberger, Mikael; Toftum, Jørn; Clausen, Geo
Abstract: Organophosphates are used in a wide range of materials and consumer products and are ubiquitous in indoor environments. Certain organophosphates have been associated with various adverse health effects. The present paper reports mass fractions of organophosphates in dust samples collected from 500 bedrooms and 151 daycare centers of children living in Odense, Denmark. The identified compounds include: tris(isobutyl) phosphate (TIBP), tri- n -butyl phosphate (TNBP), tris(2-chloroethyl) phosphate (TCEP), tris(2-chloroisopropyl) phosphate (TCIPP), tris(1, 3-dichloroisopropyl) phosphate (TDCIPP), tris(2-butoxyethyl) phosphate (TBOEP), triphenylphosphate (TPHP), 2-ethylhexyl-diphenyl phosphate (EHDPP), tris(2-ethylhexyl) phosphate (TEHP) and tris(methylphenyl) phosphate (TMPP). Both the number of organophosphates with median values above the limit of detection and the median values were higher for samples from daycare centers than for samples from homes. Organophosphates with median mass fractions above the limit of detection were: TCEP from homes (6.9 μg g −1 ), and TCEP (16 μg g −1 ), TCIPP (5.6 μg g −1 ), TDCIPP (7.1 μg g −1 ), TBOEP (26 μg g −1 ), TPHP (2.0 μg g −1 ) and EHDPP (2.1 μg g −1 ) from daycare centers. When present, TBOEP was typically the most abundant of the identified OPs. The sum of the organophosphate dust mass fractions measured in this study was roughly in the mid-range of summed mass fractions reported for dust samples collected in other countries. On a global scale, the geographical distribution of organophosphates in indoor dust is quite variable, with higher concentrations in industrialized countries. This trend differs from that for phthalate esters, whose geographic distribution is more homogeneous. Exposure to organophosphates via dust ingestion is relatively low, although there is considerable uncertainly in this assessment. Highlights: Organophosphates were determined in dust from 497 homes and 151 daycare centers. Mass fractions in dust from daycare centers were larger than in dust from homes. Estimated exposures to organophosphates via dust ingestion were relatively low. The country-to-country distribution of organophosphates is more variable than that of phthalate esters.